2022
DOI: 10.1186/s12891-022-05233-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between weather and utilisation of physical therapy in patients with osteoarthritis: a case-crossover study

Abstract: Background During varied weather conditions, patients with osteoarthritis experience different severity of symptoms and signs. However, weather may also cause barriers or incentives for patients to seek medical services. These factors may result in changes in medical utilisation; however, no studies have investigated whether the probability of physical therapy utilisation among patients with osteoarthritis is associated with changes in meteorological factors. Meth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…The rise in temperatures above 23 degrees Celsius makes it easier for patients to move around and increases the demand for physical therapy treatment. In our research, the corresponding issue was not observed, given that temperature changes are not accompanied by extreme weather phenomena [24]. Palstam et al (2021) [37] reported that the value of physical therapy is a function of effectiveness in patients versus the sum of environmental, social, and psychological factors.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The rise in temperatures above 23 degrees Celsius makes it easier for patients to move around and increases the demand for physical therapy treatment. In our research, the corresponding issue was not observed, given that temperature changes are not accompanied by extreme weather phenomena [24]. Palstam et al (2021) [37] reported that the value of physical therapy is a function of effectiveness in patients versus the sum of environmental, social, and psychological factors.…”
Section: Discussionmentioning
confidence: 57%
“…It is also possible that low barometric pressure activates the body's baroreceptors [15]. Often, an increase in barometric pressure or a change in ambient temperature, as well as increased humidity, cause a decrease in the path of pain and changes in the viscosity of synovial fluid, reducing its production and eliminating the elasticity of the already affected peri-articular structures [24]. Apart from weight receivers, both low but also high ambient temperatures with a high relative humidity activate the thermoreceptors of the skin with the parallel secretion of inflammatory substances (endothelial growth factor, interleukin-1 [IL-1]), creating or increasing inflammation in the joints [19].…”
Section: Mechanisms In Chronic Disease Sufferersmentioning
confidence: 99%
“…It appears that increased barometric pressure intensifies discomfort, impacting these patients due to lower pain thresholds. Cold temperatures elevate synovial fluid viscosity and alter periarticular structures’ compliance, making joints stiffer and more sensitive to mechanical stress during activities [ 53 ]. These factors aggravate osteoarthritis symptoms, affecting patient mobility and healthcare accessibility [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that heat sensitivity also influences anxiety is concerning given its negative impact on quality of life (Chuquilín-Arista et al 2020 ). Regarding arthritis, previous research has demonstrated an influence of hot weather on arthritis pain (Aikman 1997 ; Timmermans et al 2015 ), and access to physical therapy for arthritis pain increases in heat (Wu et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%